Application Design Go-DES with ADDIE for Implementation the Digital Economy Sharia-Based - Billy Nugraha; Soma Satria; Gading Adithia Famella (SEKOLAH TINGGI TEKNOLOGI INDUSTRI PADANG, 2024)
2021 is the year of the projection to the Indonesian government in the planning of the largest digital economy in Southeast Asia. Therefore, the development and deployment of human resources quality is the main key to achieve the largest digital economy. The initial step in introducing a system of digital economy in integrated from the world of education with the concept of sharia-based. The results of the research showed that the islamic economy in the last 10 years is growing rapidly. The purpose of this writing is the design and application called Go-DES (Go-Digital Economy based on Sharia) with ADDIE : (1) Analyze, (2) Design, (3) Development, (4) Implement and (5) Evaluate. The results of this paper is the design of the application and has the function of: (1) E-Bank there is a Saldo-Ku and E-Godes, as well as (2) E-Market there is an E-ATK, E-Seragam, E-Kantin and E- SPP.